TINGKAT KEPUASAAN PASIEN TERHADAP PELAYANAN KESEHATAN RAWAT INAP PADA KLINIK NATAMA KOTA TEBING TINGGI - Permata Amalia Mursyid; Putra Apriadi Siregar (CV. Adiba Aisha Amira, 2023)
Health is a state of complete physical, mental and social well-being and not merely the absence of disease or infirmity. Various social factors influence health conditions, such as individual behavior, social conditions, genetics and biology, health care, and the physical environment. This study aims to determine the level of patient satisfaction with inpatient services at the Natama clinic in the city of Cliff High. The study used a qualitative approach. This research was carried out at the Natama clinic in the city of Tegal Tinggi in July 2023. The main informants in this study were the Natama clinic staff and patients who were around the Natama clinic. From the results of the study, we can see that patients are quite satisfied with the services provided by health workers at the Natama clinic. However, the set completion time is not in accordance with operational standards because of the uncertain number of patients per day and the lack of serving staff. Good health services are not only given to the closest people but also given to people who really need them.